Analysis of Binder Material and Concentration on the Combustion Rate of Organic Waste Briquettes in Blitar - Yuliarochma Pratiwi; Ulfa Niswatul Khasanah; Kartika Wulandary (Indonesian Journal of Engineering, Science and Technology, 2025)
Global energy crisis and the increasing amount of organic waste require innovative and environmentally friendly waste management solutions that can also provide alternative energy sources simultaneously. This study aims to analyze the effect of the type and concentration of binder on the burning rate of organic waste briquettes produced by the Blitar City Environmental Agency. The raw material used is dry leaves mixed with organic binders, namely dextrin and tapioca, with concentrations of 10%, 20%, and 30% respectively. The briquette production process includes drying, grinding, mixing with the binder, pressing, and testing through density measurement and burning rate analysis. The study results show that the type and concentration of the binder significantly affect the performance of the briquettes. An increase in tapioca binder concentration leads to a gradual increase in the burning rate, indicating its role as a combustible component. In contrast, higher dextrin concentration reduces the burning rate but extends the burning duration, with the lowest burning rate observed in sample A3. The optimal variation was achieved using tapioca binder at a concentration of 20% (sample B2), which produced a stable burning rate. These findings contribute to the development of more efficient biomass briquette technology by providing guidance on selecting the appropriate type and proportion of binder to enhance fuel performance.   Keywords- Binder Concentration, Binder Type, Briquettes, Combustion Rate, Organic Waste.